A case report on an incidental discovery of congenital portosystemic shunt. Issue 31 (August 2019) - Păcurar, Daniela; Dijmărescu, Irina; Dijmărescu, Adrian Dumitru; Romaşcanu, Mihai; Becheanu, Cristina Adriana
Abstract: Rationale: Congenital portosystemic shunt (Abernethy malformation) is a rare entity causing the portal blood to drain directly into the systemic circulation, eluding the liver. These shunts arise through disturbances in the embryonic development. Patient concerns: A 9-year-old male patient was referred to our department for further evaluation of a vascular malformation which was diagnosed in another facility when the patient was 2 years old, following a routine abdominal ultrasound. The patient had no complaints and the physical examination was normal at all times. Diagnosis: Laboratory tests and esogastroduodenoscopy were normal. The abdominal ultrasound showed a side-to-side shunt between a short portal trunk and the inferior vena cava. A hepatic mass suggestive for focal noduar hyperplasia was seen in the left liver lobe. Abdominal angio-computed tomography (angio-CT) was performed and the ultrasonographic anomalies were confirmed. Multiple other vascular malformations were diagnosed—hepatic artery emerging from the superior mesenteric artery, with early division; hepatic veins forming a short common trunk before draining into the inferior vena cava; supranumerary right renal artery emerging from the aorta, tributary for the upper renal pole. Ecocardiography showed left superior vena cava persistence. The final diagnosis was Abernathy malformation type IB. In the meantime the patient was diagnosed with allergic asthma. Interventions: No surgical cure was pursued because the malformation was an incidental discovery. Outcomes: The patient was followed-up closely from the final diagnosis (when he was 9 years old) to present (he is currently 10 years old) with no change in his status—he remained asymptomatic. Lessons: Angio-CT should be the performed whenever a vascular malformation is suspected in order to establish a correct diagnosis, because portosystemic shunts carry a high risk of severe complications. Knowing that patients with portosystemic shunts may have pulmonary hypertension, respiratory complaints should be carefully evaluated—in this particular case, even though the most probable cause for the respiratory symptoms was pulmonary hypertension, it was ruled out by cardiac ultrasonography and further investigations confirmed the diagnosis of allergic asthma.